Effect and mechanism of acupuncture on Alzheimer’s disease: A review - Wu, Liu; Dong, Yuting; Zhu, Chengcheng; Chen, Yong (Frontiers in Aging Neuroscience, 2023)
This paper summarizes the experimental studies on acupuncture and moxibustion in the treatment of Alzheimer's disease (AD) in recent years and expounds on the related indexes of the neurobiochemical mechanism of acupuncture and moxibustion in the treatment of AD, as well as the latest progress of acupuncture and moxibustion in the field of AD mechanism and intervention research. The acupuncture treatment of AD-related indicators further verifies the effectiveness of acupuncture treatment.